A cyberlearning platform for enhancing undergraduate engineering education in sustainable product design. (20th February 2019) - Raoufi, Kamyar; Park, Kijung; Hasan Khan, Md Tarique; Haapala, Karl R.; Psenka, Carolyn E.; Jackson, Kathy L.; Okudan Kremer, Gül E.; Kim, Kyoung-Yun
Abstract: Existing tools for educating undergraduate students about sustainable engineering methods are notably lacking. In particular, these tools are unable to support the assessment of competing objectives in the evaluation of economic, environmental, and social performance across the lifecycle during product design. In an effort to address this deficiency, an interactive, web-based learning environment, a distributed cyberlearning environment, Constructionism in Learning: Sustainable Life Cycle Engineering (CooL:SLiCE) has been created. CooL:SLiCE aims to facilitate the consideration of different human controlled/initiated impacts on the natural environment through personalized individual and team-based design activities. Thus, CooL:SLiCE enables constructionist (physical, hands-on) learning in engineering via a virtual platform that allows students to visualize/analyze the effect of changes to product designs, manufacturing processes, and supply chain configurations on sustainability performance. The overall conceptual framework of the CooL:SLiCE platform is discussed. Additionally, the application of constructionism as a pedagogical approach for sustainable engineering education is presented. The framework is designed to facilitate attainment of deeper conceptual understanding in environmentally responsible product design and manufacturing by supplying a set of tools that support a constructivist learning environment. This tool set is based on disparate methodologies from the design, industrial, and manufacturing engineering domains. A team project was undertaken to pilot the CooL:SLiCE platform to aid design and assessment during the sustainable product development process. The pilot project demonstrated the capacity of the CooL:SLiCE platform in the understanding of sustainable product design concepts. This research advances the current educational tools for sustainable product design by integrating three learning modules into a web-based environment developed in the CooL:SLiCE project to provide a platform for learning not currently accessible to engineering educators and students. Future work will mainly focus on using the platform in the classroom settings to investigate its effect on improving student understanding of sustainable life cycle engineering. Highlights: Computer tools can support the constructionist learning method in esign education. Distributed cyberlearning platforms can be used for team-based and individual design. Modeling and visualization extended with sustainability analysis in a web platform. A manufacturing analysis module enables evaluation of process and supply chain impact. A supplier selection module enables identification of the best product architectures.